PERANCANGAN DAN EVALUASI SISTEM EMBER TUMPUK UNTUK PENGELOLAAN SAMPAH ORGANIK RUMAH TANGGA: Perancangan dan Evaluasi Sistem Ember Tumpuk Untuk Pengelolaan Sampah Organik - Tari Sasim, Desilvi Ayu; Wulandari, Annisa Ayuningtyas; Arbiatun, Fatimah; Mirino, Tracey Precilia (Casuarina: Jurnal Teknik Lingkungan, 2025)
This research aims to design and evaluate a stacked bucket system as a simple solution for managing household organic waste. The research method was carried out experimentally with a quantitative approach, involving the stages of preparation, manufacture and evaluation of the use of stacked buckets. The research results showed that the stacked bucket design equipped with a hole in the bottom and a tap to drain the leachate could function well. However, the success of this system was disrupted by failures in the composting process due to the condition of the organic waste being too dry and the lack of routine checks during fermentation. However, this research succeeded in identifying important factors such as humidity and the use of EM4 fluid to support the activity of microorganisms in the decomposition process. With further optimization, stacked buckets have the potential to become an effective, environmentally friendly and sustainable organic waste management method.